Frequency of modifiable cardio-vascular risk factors such as obesity, diabetes mellitus and hypertension in a Benin rural area - Zannou, D.M.; Agbodande, K.A; Azon-Kouanou, A.; Wanvoegbe, F.A.; Codjo, L; DOVONOU, A; Baglo, D.P.T; Houngbe, F. (My University, 2015)
Résumé The fight against cardiovascular diseases requires the knowledge of their modifiable risk factors.This study aimed to assess the level of modifiable cardiovascular risk factors in a rural area in orderto develop a prevention program. Methods: This is an analytical and cross-sectional study ondata collected during a fairground medical consultation of adults from 20 to 25 May 2013, in bothborder districts of the municipality of Djidja (Agouna and Houto). The studied parameters werethe capillary blood glucose profile, blood pressure profile, waist circumference (WC) and BodyMass Index (BMI). Diabetes is defined by a fasting blood glucose ≥ 1.26 g/L two times. Hypertensionis defined according to the criteria of JNC VII and obesity by BMI ≥ 30 kg/m2; abdominal obesity isdefined by a WC above 102 cm in men and 88 cm in women. Data were analyzed using SPSS softwareversion 18.0. Results: A total of 926 people were included among whom 57.8% were women. The average age was 38.43 ± 15.84 years. The prevalence of diabetes mellitus was 2.9%. The prevalenceof obesity (BMI ≥ 30 kg/m2) was 8.4%; 10.8% of studied population had abdominal obesityand 19.2% had hypertension. Age above 35 years and obesity were significantly associated withhypertension. Risk factors of obesity (IMC ≥ 30 kg/m2) were the place of residence (Agouna), thefemale gender, age between 35 and 64 and abdominal obesity. Conclusion: The frequency of cardiovascularrisk factors, although small compared to the national level, remains a concern in theinvestigated rural communities. This must lead to undertake a survey on the lifestyle and dietaryhabits of the inhabitants of these areas.
Keywords: Rural Area; Cardiovascular Risk Factors; Diabetes Mellitus; Hypertension; Obesity